Long-Lasting Exendin-4-Coated Gold Nanoparticles: Synthesis and In Vivo Evaluation of Hypoglycemic Activity - Reeju Amatya; Amala Joseph; Gu Seob Roh; Yassmine Benmokadem; Kyoung Ah Min; Meong Cheol Shin (MDPI AG, 2024)
Background: Gold nanoparticles (NPs) have drawn great attention in the area of biomedical research with their relatively safe and versatile properties. This study aimed to synthesize long-lasting exendin-4-coated gold NPs (EX-ABD-AFF-GoldNPs) and evaluate their anti-diabetic effects in vivo. Methods: In the present study, EX-ABD-AFF-GoldNPs were synthesized using a simple one-step aqueous reduction method. The physical characterization of the prepared particles verified the successful formation of the EX-ABD-AFF-GoldNPs through dynamic light scattering (DLS), transmission electron microscopy (TEM), ultraviolet-visible (UV-VIS) light spectroscopy, and Fourier transform infrared spectroscopy (FTIR). The anti-hyperglycemic and anti-obesity effects were assessed in high-fat diet (HFD)-fed obese diabetic mice. Additionally, pharmacokinetics (PK) and biodistribution studies were performed to verify the long-lasting properties. Results: The EX-ABD-AFF-GoldNPs were conglomerates of smaller globular-shaped particles, and the average size was 110(±14) nm, based on the TEM images. Safety assessments using Min6, HepG2, and B16F10 cell lines demonstrated low cytotoxicity, with over 80% cell viability up to the highest tested concentration of 150 μg/mL (as EX-ABD-AFF). Notably, the animal studies showed that the EX-ABD-AFF-GoldNPs exhibited significant hypoglycemic activity, comparable to the EX-ABD-AFF, in the HFD-fed mice. A 4-week treatment with EX-ABD-AFF-GoldNPs produced similar reductions in blood glucose and body weight to the EX-ABD-AFF, without any apparent toxicity. Furthermore, the PK and biodistribution study results confirmed the long-lasting properties (plasma half-life: 43.6 h) of the particles. Conclusions: Overall, this study demonstrated that the preparation of therapeutic protein-loaded gold NPs is feasible and, despite their much larger size compared with the protein, EX-ABD-AFF-GoldNPs can be successfully absorbed through the subcutaneous route and show nearly equivalent hypoglycemic activity to the EX-ABD-AFF protein. Finally, this study showed that long-lasting properties could be acquired by only coating EX-ABD-AFF onto gold NPs.